Peculiarities of Social Responsibility of Future Sport Pedagogues’ in the Context of Social Training - Malinauskas, Romualdas (Acta Paedagogica Vilnensia, 2002)
Scientific problem refers to the lack of investigations that provide answers to the question what social responsibility of sport pedagogues before social training and after it is. The purpose of the research is to define the peculiarities of social responsibility of future sport pedagogues in the context of social training. The following research methods have been applied in the study: Rotter scale (questionnaire), modified Dembo-Rubinstein method, which was offered to estimate peculiarities of social responsibility. The investigation was organised in two stages. In 1997, 142 future sport pedagogues of the Faculty of Pedagogy, Lithuanian Academy of Physical Education, were tested. In 2000, the same investigation was repeated. The investigation was performed with the same students. In general, 139 future pedagogues returned the questionnaires. Statistically, it has been established that control of interpersonal relations, control of career of the students were significantly high (p < 05) after the social training. Research data prove that after social training the social responsibility of future pedagogues were estimated positively (p < 05).